A 4A zeolite-Cu / polymer Fenton catalytic membrane, its preparation and application, and wastewater treatment method

By embedding copper catalysts in the pores of the polymer-based membrane, the 4A zeolite-Cu/polymer Fenton catalytic membrane solves the problem of the narrow pH applicability range of traditional Fenton technology, and achieves efficient catalytic degradation of organic pollutants in a wide pH range, with high flux and good continuous catalytic performance.

CN115888805BActive Publication Date: 2025-10-03TIANJIN DINGXIN MEMBRANE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211561249.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-07
Publication Date
2025-10-03
Estimated Expiration
2042-12-07

AI Technical Summary

Technical Problem

The traditional Fenton technology has a narrow pH application range, which leads to waste of oxidants and loss of iron ions, forming solid sludge, and has economic and environmental disadvantages.

Method used

A 4A zeolite-Cu/polymer Fenton catalytic membrane is used. By embedding a copper catalyst in the pores of the polymer-based membrane and replacing Fe2+ with Cu2+, the H2O2 reaction is catalyzed under neutral and alkaline conditions to improve the catalytic activity. 4A zeolite is used as a carrier of the copper catalyst to grow the copper catalyst in situ.

Benefits of technology

Efficient catalytic degradation of organic pollutants is achieved in a wide pH range. The catalytic membrane has a high flux and good continuous catalytic performance, avoiding the pollution problem of the homogeneous Fenton reaction, and the catalytic degradation efficiency reaches more than 90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888805B_ABST
    Figure CN115888805B_ABST
Patent Text Reader

Abstract

The present invention provides a 4A zeolite-Cu / polymer Fenton catalytic membrane and its preparation and application, and a wastewater treatment method, belonging to the technical field of wastewater treatment. The catalytic membrane of the present invention is a Fenton-like catalytic membrane, which utilizes Cu 2+ Replacement of Fe catalyst in Fenton system 2+ Cu can react with H2O2 under both neutral and alkaline conditions, with better catalytic activity and faster reaction rate. 4A zeolite is used as the carrier of the copper catalyst, allowing the copper catalyst to grow in situ on the surface of 4A zeolite. The in situ growth can better disperse the catalyst in the polymer matrix, allowing the copper catalyst to be embedded in the pores of the polymer-based membrane. The surface structure has a high exposure rate, providing a large number of active sites for the catalysis of organic pollutants, thus overcoming the disadvantage of the narrow pH range of application in the traditional Fenton reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wastewater treatment, and in particular to a 4A zeolite-Cu / polymer Fenton catalytic membrane, a preparation and application thereof, and a wastewater treatment method. Background Art

[0002] Water is one of the world's most valuable and important resources. However, with the accelerated development of urbanization and industrialization, the continued discharge of organic pollutants into water, causing environmental pollution, has become a global concern. Fenton and Fenton-like technologies, with their extremely high oxidation capacity and the final products being H2O and CO2, are environmentally friendly technologies with broad application prospects in wastewater treatment.

[0003] However, the traditional Fenton process requires acidic conditions, which can lead to waste of oxidants, iron ion loss, and the formation of solid sludge, resulting in economic and environmental drawbacks. Therefore, there is an urgent need to improve the narrow pH range of the traditional Fenton process. Summary of the Invention

[0004] The purpose of the present invention is to provide a 4A zeolite-Cu / polymer Fenton catalytic membrane and its preparation and application, as well as a wastewater treatment method, which overcomes the disadvantage of the traditional Fenton reaction having a narrow pH application range.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a 4A zeolite-Cu / polymer Fenton catalytic membrane, comprising a polymer-based membrane and a copper catalyst embedded in the pores of the polymer-based membrane. The copper catalyst comprises a 4A zeolite carrier and a copper active component loaded on the 4A zeolite carrier.

[0007] Preferably, the mass of the copper catalyst is 5 to 20% of the mass of the catalytic membrane; and the loading amount of the copper active component on the 4A zeolite carrier is 10 to 50 wt%.

[0008] The present invention provides a method for preparing the 4A zeolite-Cu / polymer Fenton catalytic membrane described in the above technical solution, comprising the following steps:

[0009] Mixing 4A zeolite, a porogen, a dispersing solvent, and a polymer, and dispersing the mixture to obtain a 4A zeolite-polymer dispersion;

[0010] Using the 4A zeolite-polymer dispersion as a casting solution, forming a film in a coagulation bath to obtain a 4A zeolite-polymer blend membrane;

[0011] The 4A zeolite-polymer blend membrane is mixed with a copper salt solution and loaded to obtain a 4A zeolite-Cu / polymer Fenton catalytic membrane.

[0012] Preferably, the porogen is at least one of polyethylene glycol, octanol, glycerol, isobutyl alcohol and polyvinyl pyrrolidone, the dispersing solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone, and the polymer is at least one of polyether sulfone, polysulfone, sulfonated polysulfone, polysulfonated polyether sulfone, tetrafluoroethylene and polyvinylidene fluoride.

[0013] Preferably, the mass ratio of the 4A zeolite to the polymer is (5-50):100; the mass ratio of the porogen, 4A zeolite and the dispersing solvent is 24:(1.6-8):(52-58.4).

[0014] Preferably, the humidity of the film-forming environment is 50-90%, the coagulation bath is pure water, and the temperature of the coagulation bath is 20-40°C.

[0015] Preferably, the copper ion concentration in the copper salt solution is 1-5 g / L, the loading time is 12-48 h; and the mass ratio of copper ions to 4A zeolite in the copper salt solution is (0.2-1):(1.6-8).

[0016] The present invention provides the use of the 4A zeolite-Cu / polymer Fenton catalytic membrane described in the above technical solution or the 4A zeolite-Cu / polymer Fenton catalytic membrane prepared by the preparation method described in the above technical solution in catalytic degradation of organic pollutants in wastewater.

[0017] The present invention provides a method for treating organic pollutants in wastewater, comprising the following steps:

[0018] Under the condition of pH = 2 to 9, wastewater containing organic pollutants, hydrogen peroxide and a catalytic membrane are compounded for catalytic degradation; the catalytic membrane is the 4A zeolite-Cu / polymer Fenton catalytic membrane described in the above technical scheme or the 4A zeolite-Cu / polymer Fenton catalytic membrane prepared by the preparation method described in the above technical scheme.

[0019] Preferably, the concentration of the hydrogen peroxide in the wastewater containing organic pollutants is 10 to 40 mM; the organic pollutants include phenolic compounds and / or dyes, the phenolic compounds include at least one of phenol, hydroquinone, bisphenol A, trichlorophenol and phloroglucinol, and the dyes include at least one of Congo red, sunset yellow, Coomassie brilliant blue, crystal violet and lemon yellow.

[0020] The present invention provides a 4A zeolite-Cu / polymer Fenton-like catalytic membrane, comprising a polymer-based membrane and a copper catalyst embedded in the pores of the polymer-based membrane, wherein the copper catalyst comprises a 4A zeolite carrier and a copper active component supported on the 4A zeolite carrier. The catalytic membrane of the present invention is a Fenton-like catalytic membrane, which utilizes Cu 2+ Replacement of Fe catalyst in Fenton system 2+ , better catalytic activity and faster reaction rate (Cu can react with H2O2 under neutral and alkaline conditions: Cu 2+ +H2O2→Cu + +HO2·+H + 、Cu + +H2O2→Cu 2+ +·OH+OH); and using 4A zeolite as a carrier of the copper catalyst, the copper catalyst is grown in situ on the surface of the 4A zeolite. The in situ growth can better disperse the catalyst in the polymer matrix, so that the copper catalyst is embedded in the pores of the polymer-based membrane. The surface structure has a high exposure rate, providing a large number of active sites for the catalysis of organic pollutants, thereby overcoming the disadvantage of the narrow pH range of application in the traditional Fenton reaction.

[0021] The catalytic membrane of the present invention uses a high molecular polymer membrane as a base membrane. The prepared catalytic membrane can be used for catalytic degradation of organic pollutants and has a high flux of 300 to 500 L·m -2 ·h -1 , the residence time of organic pollution and catalyst is long, and it has good continuous catalytic performance under high pH conditions.

[0022] The present invention provides a method for preparing the 4A zeolite-Cu / polymer Fenton catalytic membrane. The present invention adopts a non-solvent-induced phase separation method to prepare the 4A-Cu / polymer Fenton catalytic membrane. The preparation method is simple and easy to operate.

[0023] The method of the present invention can embed the catalyst into the pores of the polymer membrane, avoiding the pollution problem of the powder catalyst of the homogeneous Fenton reaction. The use of a catalytic membrane reactor for cyclic catalysis under pressure drive can also effectively solve the problem that the heterogeneous Fenton reaction is difficult to catalyze continuously.

[0024] The 4A zeolite-Cu / polymer Fenton-like catalytic membrane prepared by the present invention is used for catalytic degradation of organic pollutants in wastewater. The removal rate of organic pollutants in wastewater reaches over 90% through the Fenton-like reaction, providing a new method for wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron micrograph of a cross section of the original polyethersulfone membrane prepared in Comparative Example 1;

[0026] Figure 2 This is a cross-sectional scanning electron micrograph of the 4A-Cu / polymer Fenton catalytic membrane prepared in Example 1;

[0027] Figure 3 This is the XPS graph of the 4A-Cu / polymer Fenton catalytic film prepared in Example 1;

[0028] Figure 4 This is a schematic diagram of a reaction device for the dynamic cycle degradation of organic pollutants in wastewater;

[0029] Among them, 1-wastewater containing organic pollutants; 2-pump; 3-membrane pool; 4-catalytic membrane; 5-valve; 6-sampling port. DETAILED DESCRIPTION

[0030] The present invention provides a 4A zeolite-Cu / polymer Fenton catalytic membrane, comprising a polymer-based membrane and a copper catalyst embedded in the pores of the polymer-based membrane. The copper catalyst comprises a 4A zeolite carrier and a copper active component loaded on the 4A zeolite carrier.

[0031] The 4A zeolite-Cu / polymer Fenton catalytic membrane provided by the present invention includes a polymer-based membrane; the polymer in the polymer-based membrane is preferably at least one of polyethersulfone, polysulfone, sulfonated polysulfone, polysulfonated polyethersulfone, tetrafluoroethylene and polyvinylidene fluoride; when the polymer in the polymer-based membrane is two or more of the above-mentioned polymers, the present invention has no special restrictions on the ratio of different types of polymers, and any ratio is acceptable.

[0032] The present invention uses a polymer membrane as a substrate, and the polymer membrane has good mechanical properties and acid-base tolerance, so that the catalytic membrane can have the advantages of both Fenton reaction and membrane.

[0033] The 4A zeolite-Cu / polymer Fenton catalytic membrane provided by the present invention includes a copper catalyst embedded in the pores of the polymer-based membrane; the copper catalyst includes a 4A zeolite carrier and a copper active component loaded on the 4A zeolite carrier. The present invention does not specifically limit the source or specifications of the 4A zeolite used in the 4A zeolite carrier, and any commercially available product known in the art can be used. 4A zeolite has a high specific surface area and pores of uniform size, and has great openness. Alkali metals are evenly distributed in the pores, and there is a mutual electrostatic interaction between the pores and the skeleton to maintain the stability of the skeleton. When the zeolite molecular sieve contacts the metal salt solution, ion exchange occurs, and the metal cations in the solution are exchanged with the metal cations in the zeolite molecular sieve skeleton. The cations in the zeolite molecular sieve skeleton are exchanged and enter the solution, and the metal cations in the solution enter the skeleton structure of the zeolite molecular sieve.

[0034] In the present invention, the copper active component preferably includes copper oxide and copper hydroxide.

[0035] In the present invention, the mass of the copper catalyst is 5 to 20% of the mass of the catalytic membrane, more preferably 5.72 to 11.31%, and further preferably 6.81 to 10.05%; the loading amount of the copper active component on the 4A zeolite carrier is 10 to 50 wt%, more preferably 19.07 to 37.7 wt%, and further preferably 22.7 to 33.5 wt%.

[0036] The present invention provides a method for preparing the 4A zeolite-Cu / polymer Fenton catalytic membrane described in the above technical solution, comprising the following steps:

[0037] Mixing 4A zeolite, a porogen, a dispersing solvent, and a polymer, and dispersing the mixture to obtain a 4A zeolite-polymer dispersion;

[0038] Using the 4A zeolite-polymer dispersion as a casting solution, forming a film in a coagulation bath to obtain a 4A zeolite-polymer blend membrane;

[0039] The 4A zeolite-polymer blend membrane is mixed with a copper salt solution and loaded to obtain a 4A zeolite-Cu / polymer Fenton catalytic membrane.

[0040] In the present invention, unless otherwise specified, the raw materials required for preparation are all commercially available products well known to those skilled in the art.

[0041] The invention mixes 4A zeolite, a porogen, a dispersing solvent and a polymer, and disperses the mixture to obtain a 4A zeolite-polymer dispersion.

[0042] In the present invention, the porogen is preferably at least one of polyethylene glycol, octanol, glycerol, isobutyl alcohol, and polyvinyl pyrrolidone; the polyethylene glycol is more preferably polyethylene glycol-400; the dispersing solvent is preferably at least one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone; and the polymer is preferably at least one of polyethersulfone, polysulfone, sulfonated polysulfone, polysulfonated polyethersulfone, tetrafluoroethylene, and polyvinylidene fluoride. When the porogen, dispersing solvent, or polymer is two or more of the above, the present invention does not specifically limit the ratio of the different types of porogens, dispersing solvents, or polymers; any ratio may be used.

[0043] The present invention utilizes a porogen to promote the formation of a pore structure in a polymer film, and the function of the dispersing solvent is to form a solvent and a non-solvent system during the film-forming process.

[0044] In the present invention, the mass ratio of the 4A zeolite to the polymer is preferably (5-50):100, more preferably (10-40):100, and even more preferably (20-30):100. The present invention precisely defines the mass ratio of the 4A zeolite to the polymer to avoid a ratio lower than 5:100, which would prevent the in-situ growth of the catalyst on the 4A zeolite surface; and to avoid a mass ratio higher than 50:100, which would cause the catalyst to agglomerate in the membrane pores, reduce the exposure of active sites, and affect catalytic activity.

[0045] In the present invention, the mass ratio of the porogen, 4A zeolite and dispersing solvent is preferably 24:(1.6-8):(52-58.4), more preferably 24:(1.6-4.8):(55.2-58.4).

[0046] In the present invention, the process of mixing the 4A zeolite, porogen, dispersing solvent and polymer is preferably as follows: 4A zeolite and porogen are added to a dispersing solvent, ultrasonically dispersed to obtain a 4A zeolite dispersion; polymer is added to the 4A zeolite dispersion, stirred, and ultrasonically degassed to obtain a 4A zeolite-polymer dispersion. The present invention does not particularly limit the specific conditions of the ultrasonic dispersion, stirring and ultrasonic degassed, and can be adjusted according to actual needs; in an embodiment of the present invention, specifically ultrasonic dispersion for 0.5h, stirring for 12h, and ultrasonic degassed for 0.5h.

[0047] After obtaining the 4A zeolite-polymer dispersion, the present invention uses the 4A zeolite-polymer dispersion as a casting liquid to form a membrane in a coagulation bath to obtain a 4A zeolite-polymer blend membrane.

[0048] The present invention preferably employs a non-solvent-induced phase separation method for film formation. The coagulation bath is preferably pure water. The present invention does not specifically limit the amount of the coagulation bath used; it can be used in accordance with procedures well known in the art to ensure film formation. The humidity of the film formation environment is preferably 50-90%, more preferably 60%. The temperature of the coagulation bath is preferably 20-40°C, more preferably 25°C. Controlling the above film-forming conditions facilitates the formation of a porous structure, allowing the catalyst to better embed within the pores of the polymer-based membrane and effectively catalyze the degradation of organic pollutants.

[0049] In the membrane formation process using the non-solvent induced phase separation method, when the casting liquid enters the coagulation bath, the solvent and non-solvent (coagulation bath) diffuse into each other through the liquid film / coagulation bath interface. The exchange between the solvent and the non-solvent reaches a certain level. At this time, the casting liquid becomes a thermodynamically unstable system, resulting in phase separation of the casting liquid. After phase separation, the solvent and the non-solvent further exchange, resulting in the coagulation of membrane pores, interphase flow, and the polymer-rich phase forming the main structure of the membrane, while the polymer-poor phase forms membrane pores, and finally solidifies into a membrane.

[0050] After obtaining the 4A zeolite-polymer blend membrane, the present invention mixes the 4A zeolite-polymer blend membrane with a copper salt solution and loads the membrane to obtain a 4A zeolite-Cu / polymer Fenton catalytic membrane.

[0051] In the present invention, the copper salt in the copper salt solution is preferably copper chloride; the copper ion concentration in the copper salt solution is preferably 1 to 5 g / L, more preferably 2 g / L; the loading time is preferably 12 to 48 hours, more preferably 24 hours; the mass ratio of copper ions to 4A zeolite in the copper salt solution is (0.2 to 1):(1.6 to 8), more preferably 0.4:4.8. The present invention does not specifically limit the method of mixing the 4A zeolite-polymer blend membrane with the copper salt solution, and any method known in the art can be used. Specifically, the present invention involves immersing the 4A zeolite-polymer blend membrane in the copper salt solution.

[0052] During the loading process, copper ions interact with the Al-O-Si segments and combine with the hydroxides released from the 4A zeolite to form copper hydroxide nanosheets, allowing the Cu catalyst to grow in situ on the surface of the 4A zeolite.

[0053] The present invention provides the use of the 4A zeolite-Cu / polymer Fenton catalytic membrane described in the above technical solution or the 4A zeolite-Cu / polymer Fenton catalytic membrane prepared by the preparation method described in the above technical solution in catalytic degradation of organic pollutants in wastewater.

[0054] The present invention provides a method for treating organic pollutants in wastewater, comprising the following steps:

[0055] Under the condition of pH = 2 to 9, wastewater containing organic pollutants, hydrogen peroxide and a catalytic membrane are compounded for catalytic degradation; the catalytic membrane is the 4A zeolite-Cu / polymer Fenton catalytic membrane described in the above technical scheme or the 4A zeolite-Cu / polymer Fenton catalytic membrane prepared by the preparation method described in the above technical scheme.

[0056] The present invention has no special limitation on the source of the wastewater containing organic pollutants, and any wastewater containing organic pollutants known in the art can be used; the organic pollutants preferably include phenolic compounds and / or dyes, and the phenolic compounds preferably include at least one of phenol, hydroquinone, bisphenol A, trichlorophenol and phloroglucinol, and the dyes preferably include at least one of Congo red, sunset yellow, Coomassie brilliant blue, crystal violet and lemon yellow; when the organic pollutants are two or more of the above, the present invention has no special limitation on the content of different types of organic pollutants, and the content corresponding to the wastewater containing organic pollutants actually obtained is sufficient.

[0057] When treating organic pollutants, the present invention has no special restrictions on the specific amount of the catalytic membrane, which can be adjusted according to actual needs. In the application example of the present invention, the catalytic membrane is a circular membrane with an effective area of ​​15.9 cm 2 The concentration of the hydrogen peroxide is preferably 98 mM. The concentration of the hydrogen peroxide in the wastewater containing organic pollutants is preferably 10 to 40 mM, more preferably 20 to 31.6 mM. The present invention controls the concentration range of the hydrogen peroxide so that the hydrogen peroxide reacts with the catalyst to produce a sufficient amount of hydroxyl radicals, which is beneficial for catalytic degradation and has a good catalytic degradation effect on organic pollutants.

[0058] The present invention has no special limitation on the method for providing the pH condition of 2 to 9, and the above pH condition can be achieved by methods well known in the art. The present invention has a good catalytic degradation effect on organic pollutants within this pH range. A pH greater than 9 or less than 2 will affect the stability of the polymer film.

[0059] The present invention does not specifically limit the process of combining the organic pollutant-containing wastewater, hydrogen peroxide, and the catalytic membrane; it can be carried out according to procedures well known in the art. The present invention does not specifically limit the duration of the catalytic degradation; it can be adjusted according to actual needs. In the embodiments of the present invention, a simulated pollutant solution is preferably used as the organic pollutant wastewater for catalytic degradation.

[0060] The present invention uses 4A-Cu / polymer Fenton catalytic membrane as a catalyst, and utilizes hydrogen peroxide and the catalytic membrane to carry out a Fenton-like reaction under the condition of pH = 2-9 to catalytically degrade organic pollutants in wastewater, thereby overcoming the disadvantage of the traditional Fenton reaction having a narrow pH application range.

[0061] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0062] Example 1

[0063] 4.8 g of 4A zeolite and 24 g of polyethylene glycol-400 were weighed and added to 55.2 g of N,N-dimethylacetamide, and ultrasonically dispersed for 0.5 h. 16 g of polyethersulfone was added to the resulting solution, stirred for 12 h, and ultrasonically degassed for 0.5 h to obtain a 4A zeolite / polyethersulfone casting solution. The mass ratio of 4A zeolite to polyethersulfone was 30:100.

[0064] The 4A zeolite / polyethersulfone casting solution was prepared into a 4A zeolite / polyethersulfone blend membrane by a non-solvent induced phase separation method using pure water as a coagulation bath, wherein the ambient humidity was 60% and the coagulation bath temperature was 25° C., thereby obtaining a 4A zeolite / polyethersulfone blend membrane;

[0065] The 4A zeolite / polyethersulfone blend membrane was immersed in 200 mL of a copper chloride solution having a copper ion concentration of 2 g / L for 24 hours to obtain a 4A-Cu / polymer Fenton catalytic membrane, wherein the mass of the copper catalyst was 10.05% of the mass of the catalytic membrane; and the loading amount of the copper active component on the 4A zeolite carrier was 33.5 wt%.

[0066] Example 2

[0067] The only difference from Example 1 is that the mass ratio of 4A zeolite to polymer is 10:100, the mass of the copper catalyst is 5.72% of the mass of the catalytic membrane; and the loading amount of the copper active component on the 4A zeolite carrier is 19.07 wt%.

[0068] Example 3

[0069] The only differences from Example 1 are that the polymer is sulfonated polysulfone; the mass of the copper catalyst is 11.31% of the mass of the catalytic membrane; and the loading amount of the copper active component on the 4A zeolite carrier is 37.7 wt%.

[0070] Example 4

[0071] The only differences from Example 1 are: the soaking time is 12 h; the mass of the copper catalyst is 6.81% of the mass of the catalytic membrane; and the loading amount of the copper active component on the 4A zeolite carrier is 22.7 wt%.

[0072] Comparative Example 1

[0073] 16 wt% polyethersulfone, 24 wt% polyethylene glycol-400 and 60 wt% N,N-dimethylacetamide were added into a three-necked flask and stirred to obtain a casting solution, and a polyethersulfone original membrane was obtained by a non-solvent induced phase separation method.

[0074] Comparative Example 2

[0075] The catalytic membrane prepared in Example 1 was immersed in a 4 g / L ferric chloride solution for 24 hours to obtain a Fenton catalytic membrane loaded with isolated iron species / polyethersulfone.

[0076] Application Example 1

[0077] The 4A-Cu / polymer Fenton catalytic membrane prepared in Example 1 was cut into pieces with an effective area of ​​15.9 cm 2 The circular membrane is placed Figure 4In the illustrated cyclic catalytic reaction apparatus, a dynamic cyclic catalytic reaction is performed on 200 mL of a 2g / L phenol aqueous solution at room temperature and pH 2. During this process, a 4A-Cu / polymer Fenton catalytic membrane is placed in membrane reservoir 3 of the apparatus. After adding 98mM hydrogen peroxide, the dynamic cyclic catalytic process is completed using pump 2. Sampling is then performed through sampling port 6 for testing. The concentration of hydrogen peroxide in the phenol aqueous solution is 31.6mM.

[0078] Application Example 2

[0079] The difference from Application Example 1 is that pH=6.

[0080] Application Example 3

[0081] The difference from Application Example 1 is that pH=9.

[0082] Application Example 4

[0083] The 4A-Cu / polymer Fenton catalytic membrane prepared in Example 2 was cut into pieces with an effective area of ​​15.9 cm 2 The circular membrane is placed Figure 4 In the illustrated cyclic catalytic reaction apparatus, a dynamic cyclic catalytic reaction is performed on 200 mL of a 2g / L phenol aqueous solution at room temperature and pH 2. During this process, a 4A-Cu / polymer Fenton catalytic membrane is placed in the apparatus's membrane reservoir 3. After adding 98mM hydrogen peroxide, the dynamic cyclic catalytic process is completed using pump 2. Sampling is then performed through sampling port 6 for testing. The concentration of hydrogen peroxide in the phenol aqueous solution is 20mM.

[0084] Application Example 5

[0085] The 4A-Cu / polymer Fenton catalytic membrane prepared in Example 3 was cut into pieces with an effective area of ​​15.9 cm 2 The circular membrane is placed Figure 4 In the illustrated cyclic catalytic reaction apparatus, a dynamic cyclic catalytic reaction is performed on 200 mL of a 2g / L phenol aqueous solution at room temperature and pH 2. During this process, a 4A-Cu / polymer Fenton catalytic membrane is placed in membrane reservoir 3 of the apparatus. After adding 98mM hydrogen peroxide, the dynamic cyclic catalytic process is completed using pump 2. Sampling is then performed through sampling port 6 for testing. The concentration of hydrogen peroxide in the phenol aqueous solution is 31.6mM.

[0086] Application Example 6

[0087] The 4A-Cu / polymer Fenton catalytic membrane prepared in Example 4 was cut into pieces with an effective area of ​​15.9 cm 2 The circular membrane is placed Figure 4 In the illustrated cyclic catalytic reaction apparatus, a dynamic cyclic catalytic reaction is performed on 200 mL of a 2g / L Congo red aqueous solution at room temperature and pH 2. During this process, a 4A-Cu / polymer Fenton catalytic membrane is placed in membrane reservoir 3 of the apparatus. After adding 98mM hydrogen peroxide, a pump 2 is used to complete the dynamic cyclic catalytic process. Sampling is then performed through sampling port 6 for testing. The concentration of hydrogen peroxide in the Congo red aqueous solution is 31.6mM.

[0088] Comparative Application Example 1

[0089] The only difference from Application Example 2 is that the original polyethersulfone membrane prepared in Comparative Example 1 is used as the catalytic membrane.

[0090] Comparative Application Example 2

[0091] The only difference from Application Example 2 is that the isolated iron species / polyethersulfone Fenton catalytic membrane prepared in Comparative Example 2 is used.

[0092] Comparative Application Example 3

[0093] The only difference from Application Example 3 is that the isolated iron species / polyethersulfone Fenton catalytic membrane prepared in Comparative Example 2 is used.

[0094] Characterization and performance testing

[0095] 1) Electron microscopy characterization of the films prepared in Example 1 and Comparative Example 1: The films were tested using a German ZEISS Gemini SEM500 instrument with an accelerating voltage of 10 kV. Before testing, the samples were subjected to gold spraying to improve their conductivity. The results are shown in Table 1. Figures 1-2 ; Figure 1 This is a scanning electron micrograph of a cross section of the original polyethersulfone membrane prepared in Comparative Example 1; Figure 2 The following is a cross-sectional scanning electron micrograph of the 4A-Cu / polymer Fenton catalytic membrane prepared in Example 1 (a and b are scanning images at different magnifications). Figures 1-2 The cross-section of the catalytic membrane exhibits a straight, finger-like pore structure. High-magnification images reveal a good bond between the catalyst particles and the PES-based membrane, but the catalyst is not completely embedded within the PES polymer. This indicates that the catalyst is stable within the membrane while maintaining its inherent catalytic properties. Furthermore, while 4A-Cu maintains a cubic structure, its surface becomes very rough due to the assembly of numerous two-dimensional nanosheets into a three-dimensional shell.

[0096] 2) XPS test of the 4A-Cu / polymer Fenton catalytic membrane prepared in Example 1: The photoelectron spectrum of the catalyst sample was measured using a NEXSA X-ray photoelectron spectrometer produced by ThemnoFisher, USA, and the elements on its surface were qualitatively analyzed. The peak position of the test results of all samples was corrected based on the C1s=248.8eV of the external carbon source. The results are shown in Figure 2. Figure 3 .like Figure 3 As shown in the Cu2p XPS spectrum, the Cu 2p at the bonding energy of 935.1eV 3 / 2 The peak has a broad shoulder peak (about 943.2eV), and the difference in bonding energy between the two is about 8.1eV, which proves that only Cu exists in the 4A-Cu sample. 2+ . Divalent ion Cu 2+ It exists in two forms, namely CuO in the oxide (933.3 eV) and Cu(OH)2 on the surface (935.1 eV).

[0097] 3) Place the catalytic membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2 into Figure 4 The test was carried out in the reaction device shown in FIG. After 15 minutes of pre-pressing, the flux of pure water through the membrane was measured at 0.05 MPa. The calculation formula of the catalytic membrane flux J is:

[0098]

[0099] Where V is the volume of filtered water, mL; t is the test time, s; S is the effective membrane area, cm 2 ;

[0100] The results are shown in Table 1.

[0101] Table 1 Membrane flux data of catalytic membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2

[0102] Case T(s) V (mL) <![CDATA[J(L / m 2 h)]]> Example 1 35.43 6.4 408.88 Example 2 30.68 5.2 383.65 Example 3 35.43 6 383.33 Example 4 49.31 8.5 390.19 Comparative Example 1 80.07 9.1 257.25 Comparative Example 2 50.84 8 356.87

[0103] As shown in Table 1, the pure water flux of Examples 1-4 and Comparative Example 2 increased compared to the original PES membrane (Comparative Example 1). This is likely due to the increased hydrophilicity of the catalyst, which in turn increases the hydrophilicity of the catalytic membrane. The high water flux of the catalytic membrane is beneficial for pollutant treatment.

[0104] 4) The catalytic performance of the catalytic membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 2 in catalytic degradation of organic pollutants was tested. The testing method for phenolic substances was the 4-aminoantipyrine method, that is, the phenolic compound reacted with 4-aminoantipyrine in the presence of potassium ferrocyanide at a pH of about 10 to generate an orange-red indole antipyrine dye. The color was proportional to the content of the phenolic compound within a certain concentration range, and its content at different stages was determined by colorimetry.

[0105] The calculation formula for the degradation rate of organic pollutants is:

[0106]

[0107] Wherein, C is the concentration of organic pollutants after catalytic degradation reaction; C0 is the concentration of organic pollutants before catalytic degradation reaction.

[0108] The obtained data are shown in Table 2.

[0109] Table 2 Data on catalytic degradation of organic pollutants by different catalytic membranes in application examples 1 to 6 and comparative application examples 1 to 2

[0110] pH C <![CDATA[C0]]> Degradation time Degradation rate Application Example 1 2 0.019g / L 0.2g / L 5min 90.5% Application Example 2 6 0.015g / L 0.2g / L 3h 92.5% Application Example 3 9 0.01g / L 0.2g / L 9h 95% Application Example 4 2 0.019g / L 0.2g / L 60min 90.5% Application Example 5 9 0.018g / L 0.2g / L 10h 91% Application Example 6 6 0.012g / L 0.2g / L 5h 94% Comparative Application Example 1 6 0 0.2g / L 24h 0 Comparative Application Example 2 6 0.012g / L 0.2g / L 8h 94% Comparative Application Example 3 9 0.017g / L 0.2g / L 13h 91.5%

[0111] As shown in Table 2, the 4A-Cu / polyethersulfone Fenton catalytic membrane prepared by the present invention has excellent catalytic performance against organic pollutants. The catalytic membrane prepared in Example 1 (Application Example 1) has a phenol degradation rate of over 90% within 5 minutes. Under the same conditions, the catalytic membrane prepared in Example 2 (Application Example 2) has a phenol degradation rate of 92.5% within 3 hours. The catalytic membrane prepared in Comparative Example 2 (Comparative Application Example 2) has a phenol degradation rate of 94% within 8 hours. Under the condition of pH = 9, the catalytic membrane prepared in Example 1 (Application Example 3) has a phenol degradation rate of 95% within 9 hours; under the condition of pH = 9, the catalytic membrane prepared in Comparative Example 2 (Comparative Application Example 3) has a phenol degradation rate of 91.5% within 13 hours. This shows that the catalytic membrane prepared by the present invention can shorten the degradation time under alkaline conditions, that is, it can optimize the problem of the narrow pH range of the Fenton reaction.

[0112] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A 4A zeolite-Cu / polymer Fenton catalytic membrane, comprising a polymer-based membrane and a copper catalyst embedded in the pores of the polymer-based membrane, wherein the copper catalyst comprises a 4A zeolite carrier and a copper active component supported on the 4A zeolite carrier; the copper active component comprises copper oxide and copper hydroxide, wherein the copper hydroxide is copper hydroxide nanosheets; the mass of the copper catalyst is 5.72 to 11.31% of the mass of the catalytic membrane; and the loading amount of the copper active component on the 4A zeolite carrier is 19.07 to 37.7 wt%.

2. The method for preparing the 4A zeolite-Cu / polymer Fenton catalytic membrane according to claim 1, characterized in that: The following steps are involved: Mixing 4A zeolite, a porogen, a dispersing solvent, and a polymer, and dispersing the mixture to obtain a 4A zeolite-polymer dispersion; Using the 4A zeolite-polymer dispersion as a casting solution, forming a film in a coagulation bath to obtain a 4A zeolite-polymer blend membrane; The 4A zeolite-polymer blend membrane is mixed with a copper salt solution and loaded to obtain a 4A zeolite-Cu / polymer Fenton catalytic membrane.

3. The preparation method according to claim 2, characterized in that The porogen is at least one of polyethylene glycol, octanol, glycerol, isobutyl alcohol and polyvinyl pyrrolidone, the dispersing solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone, and the polymer is at least one of polyether sulfone, polysulfone, sulfonated polysulfone, polysulfonated polyether sulfone, tetrafluoroethylene and polyvinylidene fluoride.

4. The preparation method according to claim 2 or 3, characterized in that The mass ratio of the 4A zeolite to the polymer is (5-50):100; the mass ratio of the porogen, 4A zeolite and the dispersing solvent is 24:(1.6-8):(52-58.4).

5. The preparation method according to claim 2, characterized in that The film forming environment humidity is 50-90%, the coagulation bath is pure water, and the temperature of the coagulation bath is 20-40°C.

6. The preparation method according to claim 2, characterized in that The copper ion concentration in the copper salt solution is 1-5 g / L, and the loading time is 12-48 h; the mass ratio of copper ions in the copper salt solution to 4A zeolite is (0.2-1):(1.6-8).

7. Use of the 4A zeolite-Cu / polymer Fenton catalytic membrane according to claim 1 or the 4A zeolite-Cu / polymer Fenton catalytic membrane prepared by the preparation method according to any one of claims 2 to 6 in catalytic degradation of organic pollutants in wastewater.

8. A method for treating organic pollutants in wastewater, characterized in that: The following steps are involved: Under the condition of pH = 2 to 9, wastewater containing organic pollutants, hydrogen peroxide and a catalytic membrane are compounded for catalytic degradation; the catalytic membrane is the 4A zeolite-Cu / polymer Fenton catalytic membrane described in claim 1 or the 4A zeolite-Cu / polymer Fenton catalytic membrane prepared by the preparation method according to any one of claims 2 to 6.

9. The processing method according to claim 8, characterized in that: The concentration of the hydrogen peroxide in the wastewater containing organic pollutants is 10 to 40 mM; the organic pollutants include phenolic compounds and / or dyes, the phenolic compounds include at least one of phenol, hydroquinone, bisphenol A, trichlorophenol and phloroglucinol, and the dyes include at least one of Congo red, sunset yellow, Coomassie brilliant blue, crystal violet and lemon yellow.

Citation Information

Patent Citations

  • Zeolite Fenton catalyst containing isolated metal species as well as preparation method and application thereof

    CN105618129A

  • Isolated iron species / polymer loaded porous Fenton catalytic membrane as well as preparation method and application thereof

    CN109999906A